Social motor coordination during adult–child interactions. Issue 1 (4th May 2018) - Pfeiffer, Rita; Wallace, Mark; Lense, Miriam
Abstract: Social motor coordination (SMC) pertains to the timing of contingent movements during social interactions and is of high relevance for successful social and musical interactions. Semi‐automated, objective methods are increasingly being used to analyze SMC, though it is unclear if these methods are feasible in naturalistic settings with young children. The purpose of the current preliminary study was to explore SMC in adult–child dyads during semi‐structured social interactions. Thirteen dyads (mean age of children = 36 months) participated in a predictable turn‐taking task from a social communication assessment, and a semi‐automated frame‐difference approach was used to capture movement activity. Relative timing and activity approaches revealed that, while there is some evidence of co‐occurring movement, the dyad predominantly exhibited patterns of responsive movement activity (e.g., turn taking or alternating movement) consistent with the activity's structure. Future work may extend these approaches to social musical interactions in order to examine movement coordination and prosocial behavior during joint music‐making activities with young children. Abstract : Social motor coordination (SMC) pertains to the timing of movements during social interactions and is important for social and musical interactions. Here, we report a preliminary study exploring SMC in adult–child dyads during semi‐structured social interactions. Future work may extend these approaches to social musical interactions to examine movement coordination and behavior during joint music‐making activities with young children.